2014
DOI: 10.1111/ajd.12276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of insulin resistance in idiopathic hirsutism compared with polycystic ovary syndrome patients and healthy individuals

Abstract: Insulin resistance was no more frequent in IH patients than in healthy control groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…4 It is generally accepted that insulin resistance and secondary hyperinsulinemia have a pivotal role in the pathophysiology of PCOS. 5,6 The endocrine and metabolic abnormalities in patients with PCOS also affect the metabolism and function of the endometrium, which may lead to impaired endometrium receptivity, resulting in embryo implantation disorders. 7 Our previous study 8 showed that the insulin levels in endometrial epithelial cells of patients with PCOS were significantly elevated, while glucose transporter-4, an insulin-dependent intracellular glucose transporter protein, exhibited significantly reduced expression, suggesting insulin resistance in the endometrium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 It is generally accepted that insulin resistance and secondary hyperinsulinemia have a pivotal role in the pathophysiology of PCOS. 5,6 The endocrine and metabolic abnormalities in patients with PCOS also affect the metabolism and function of the endometrium, which may lead to impaired endometrium receptivity, resulting in embryo implantation disorders. 7 Our previous study 8 showed that the insulin levels in endometrial epithelial cells of patients with PCOS were significantly elevated, while glucose transporter-4, an insulin-dependent intracellular glucose transporter protein, exhibited significantly reduced expression, suggesting insulin resistance in the endometrium.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is generally accepted that insulin resistance and secondary hyperinsulinemia have a pivotal role in the pathophysiology of PCOS. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…The association between IR and IH is not clear. Bonakdaran et al (25) did not find significant differences between the levels of serum insulin and the prevalence of IR in PCOS, IH, and healthy subjects, but Unlühizarci et al (26) found an association between IR and IH. In the present study, we did not find any association between IR and IH.…”
Section: Discussionmentioning
confidence: 96%
“…Insulin resistance is defined as a defect in glucose response to a specific amount of insulin. Insulin levels increase in circulation to maintain glucose levels to compensate for this deficiency in many of these patients [13]. There is a relationship between insulin resistance and coronary heart disease [14,15].…”
Section: Introductionmentioning
confidence: 99%